When knowledge reaches the field, agriculture scales up - Borrayo Perez, Andrea Surama; Arce Gomez, Daniela (2025)
Within the CGIAR Scaling for Impact Science Program, the AgriLAC Resiliente initiative is supporting the scaling of resilient agriculture in Guatemala by ensuring that knowledge effectively reaches the field. Through the InnovaHubs, more than 200 farmers, students, and technicians have strengthened their capacities in improved agronomic practices, postharvest management, and the use of climate information to support informed and context-specific decision-making.